The ecology of the Indonesian seas (Oxford University Press, 1997)
The main objective of this book os to introduce Indonesian students to the fascinating marine environment of the Indonesian archipelago. this book provides an overview of a number of coastal and marine environments of the Indonesian Archipelago, with a focus on ecological precesses.